(untitled) (Damu Journal of Sport Sciences, 2025)
During her years of study in the Department of Physical Education and Sports Sciences at the University of Kufa and her constant presence with the supervisors in field lessons, the researcher noted the presence of some obstacles in teaching the 4 x 100m relay running activity. These obstacles included the lack of support tools in the classroom, with only simple tools available. This impacted the specification of exercises by the subject's teachers. The research aims to: prepare compound exercises, provide supportive aids, and identify the effect of compound exercises using supportive aids on some biokinetic abilities and technical performance of female students in the 4 x 100m relay event. The most important conclusions are: The duration and number of units allocated to teaching the 4 x 100m relay event were sufficient to bring about positive changes in the studied research variables. The development of the research variables had a significant impact on the development of technical performance in the female students' 4 x 100m relay event. The compound exercises contributed to improving the students' muscular strength, which helps prevent common sports injuries in relay races.